2015
DOI: 10.1001/jamaophthalmol.2015.3345
|View full text |Cite
|
Sign up to set email alerts
|

Toluidine Blue 0.05% Vital Staining for the Diagnosis of Ocular Surface Squamous Neoplasia in Kenya

Abstract: Importance Clinical features are unreliable for distinguishing Ocular Surface Squamous Neoplasia (OSSN) from benign conjunctival lesions. Objective To evaluate the adverse effects, accuracy and inter-observer variation of Toluidine Blue 0.05% vital staining in distinguishing OSSN, confirmed by histopathology, from other conjunctival lesions. Design, Setting and Participants Cross-sectional study in Kenya from July 2012 through July 2014 of 418 adults with suspicious conjunctival lesions. Pregnant and breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…For instance, for conjunctival squamous cell carcinoma, efforts to screen HIV-infected patients in Kenya using toluidine blue staining have been described [57*], as well as suggestions that resection followed by brachytherapy may be well tolerated and associated with low recurrence rates in South Africa [58*]. However, given the relatively immature nature of the field overall, there are not major recent studies for other HIVAM in LMIC that would clearly merit inclusion in this review, although it is hoped that more data related to these tumors will soon be forthcoming.…”
Section: Other Cancersmentioning
confidence: 99%
“…For instance, for conjunctival squamous cell carcinoma, efforts to screen HIV-infected patients in Kenya using toluidine blue staining have been described [57*], as well as suggestions that resection followed by brachytherapy may be well tolerated and associated with low recurrence rates in South Africa [58*]. However, given the relatively immature nature of the field overall, there are not major recent studies for other HIVAM in LMIC that would clearly merit inclusion in this review, although it is hoped that more data related to these tumors will soon be forthcoming.…”
Section: Other Cancersmentioning
confidence: 99%
“…[20] 419 adult patients underwent comprehensive ophthalmic examination including slit lamp biomicroscopy that included ocular surface staining with toluidine blue 0.05%. [20] Photographs were taken of lesions with and without staining, and masked examiners reviewed 100 consecutive photographs.…”
Section: Resultsmentioning
confidence: 99%
“…[20] 419 adult patients underwent comprehensive ophthalmic examination including slit lamp biomicroscopy that included ocular surface staining with toluidine blue 0.05%. [20] Photographs were taken of lesions with and without staining, and masked examiners reviewed 100 consecutive photographs. [20] The authors reported that toluidine blue 0.05% had a high sensitivity (92%) but low specificity (31%) for diagnosis of OSSN compared to confirmation by histopathology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations